The Influence of Global Competency Frameworks on 21st-Century Skill Development in Secondary Education - Ahmed El-Sayed; Sophia Martinez (Innovative Journal of Educational Research and Insights, 2025)
This study investigates the influence of global competency frameworks on the development of 21st-century skills among secondary school students. In the context of growing globalization, schools are increasingly integrating global competencies—such as intercultural understanding, global awareness, and collaborative problem-solving—into their curricula to better prepare students for the demands of the modern world. Using a mixed-methods approach, this research collected data from 150 students across three schools through surveys and semi-structured interviews with teachers and school leaders. Quantitative analysis using linear regression and SEM revealed that global competency significantly predicts the enhancement of communication, collaboration, critical thinking, and creativity skills among students. Additionally, qualitative findings highlighted differences in framework implementation between urban and suburban schools, with urban schools showing more frequent use of technology-driven and international programs. The study contributes to strengthening global education theory and provides practical recommendations for integrating global competency frameworks into secondary education systems